2011
DOI: 10.1186/1471-2105-12-s14-s5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis workflow for the structural and functional classification of C-type lectins

Abstract: BackgroundIt is important to understand the roles of C-type lectins in the immune system due to their ubiquity and diverse range of functions in animal cells. It has been observed that currently confirmed C-type lectins share a highly conserved domain known as the C-type carbohydrate recognition domain (CRD). Using the sequence profile of the CRD, an increasing number of putative C-type lectins have been identified. Hence, it is highly needed to develop a systematic framework that enables us to elucidate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…1B). Only one polypeptide belonging to the uncharacterized transmembrane glycan-binding receptor on dividing B cells -C-type lectin domain family 17, member A isoform 1 (CLEC17A or prolectin) protein (Koh et al, 2011) -exhibited a fold change that was similar to the values obtained for FANCD2 and FANCI.…”
Section: Identifying Proteins That Are Post-translationally Modified supporting
confidence: 62%
“…1B). Only one polypeptide belonging to the uncharacterized transmembrane glycan-binding receptor on dividing B cells -C-type lectin domain family 17, member A isoform 1 (CLEC17A or prolectin) protein (Koh et al, 2011) -exhibited a fold change that was similar to the values obtained for FANCD2 and FANCI.…”
Section: Identifying Proteins That Are Post-translationally Modified supporting
confidence: 62%
“…Interestingly the Eutirucallin treatment did not affect the viability of fibroblast and macrophage cells but did affect the viability of all tumorigenic cells lines. A previous study indicated that lectins selectively bind to malignant cells because they only bind to specific carbohydrates by recognizing domains present in cell membranes that are differentially expressed in non-tumor cells (Sharon, 2007 ; Sabova et al, 2010 ; Koh et al, 2011 ; Nolte et al, 2012 ). The internalization of lectin improves its intracellular availability and activity (Lichtenstein and Rabinovich, 2013 ).…”
Section: Resultsmentioning
confidence: 99%